Hardware/ software interactive learning for Karnaugh Map - Khor, Kai Xiang (Nanyang Technological University, 2020)
With the recent development of technology, terms like ‘Flipping classroom” have become a trend today. It is undeniable that technology has changed how students learn today. This report will outline the creation of an E-learning package that covers not only the software through a game but also the creation of hardware to further enhance the learning process of the given topic: Karnaugh Map. This report will cover techniques used to create the video with the help of Adobe illustrator as well as video editing software like Filmora. Besides the creation of the videos, this report will also discuss techniques used to programme out the game using Felgo, a cross-platform development tool that uses the Qt framework. Lastly, this report will also discuss the creation of hardware that complements the game in teaching Karnaugh Map. By combining the three learning tools – videos, game, and hardware, this E-learning package will facilitate vivid visualization as well as comprehension of concepts related to the Karnaugh map.